2013
DOI: 10.1186/1471-2377-13-190
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorders and risk of Parkinson’s disease: findings from a Swedish national cohort study 1972–2008

Abstract: BackgroundAlcohol has been suggested to be either protective of, or not associated with Parkinson’s disease (PD). However, experimental animal studies indicate that chronic heavy alcohol consumption may have dopamine neurotoxic effects relevant for PD. We studied the association between diagnosed alcohol use disorders and PD.MethodsAll individuals in Sweden admitted with a diagnosis of an alcohol use disorder or appendicitis (reference group) between January 1, 1972 and December 31, 2008 were identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…In another meta‐analysis, a weak protective association tended to be reported in case‐control studies rather than prospective cohort studies . In a prospective study from Sweden, heavy alcohol use was associated with an increased risk of PD (HR 1.38, 95% CI: 1.25–1.53, adjusted for age and sex) …”
Section: Analytical Epidemiologymentioning
confidence: 96%
“…In another meta‐analysis, a weak protective association tended to be reported in case‐control studies rather than prospective cohort studies . In a prospective study from Sweden, heavy alcohol use was associated with an increased risk of PD (HR 1.38, 95% CI: 1.25–1.53, adjusted for age and sex) …”
Section: Analytical Epidemiologymentioning
confidence: 96%
“…Smoking and caffeine consumption, two common daily behaviors, have been consistently associated with a reduced risk of PD. However, the dual roles of positive and negative results from epidemiological studies on alcohol intake and PD risk have been reported [36,37,77,78].…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…Alcohol has been suggested to be either protective of, or not associated with PD [36]. However, experimental animal studies indicate that chronic heavy alcohol consumption may have dopamine neurotoxic effects [37]. Chronic alcohol exposure decreased the levels of dopamine (DA) [38] and increased the amount of α-Synuclein (αSYN), which was linked to the development of PD [39].…”
Section: Introduction and Alcohol Use: Dual Effects And Mechanismsmentioning
confidence: 99%
“…(35, 36) A Swedish registry study that found a history of admission for alcohol abuse was associated with increased risk (HR 1.38, 1.25–1.53) of future diagnosis of PD, an intriguing finding potentially linking the biological processes of the two diseases. (37) The relationship was strongest for the younger onset population, and our previous studies of disabled younger PD patients also found an increased risk of hospitalization for substance abuse(19), together suggesting an interaction between for age and substance use disorders in PD patients.…”
Section: Discussionmentioning
confidence: 77%